2010
DOI: 10.1111/j.1582-4934.2009.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases‐1‐induced scattered liver metastasis is mediated by host‐derived urokinase‐type plasminogen activator

Abstract: Paradoxically, not only proteinases but also their inhibitors can correlate with bad prognosis of cancer patients, underlining the evolving concept of the protease web as the complex interplay between proteinases, their inhibitors and effector molecules. Elevated levels of tissue inhibitor of metalloproteinases-1 (TIMP-1) render the liver more susceptible to metastasis by triggering urokinase plasminogen activator (uPA) expression as well as hepatocyte growth factor (HGF) signalling, thereby leading to the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…It has been confirmed that TIMP-1 is regulated by Bcl-2, which participates in the cellular apoptotic pathway [8]. However, recent reports indicate that TIMP-1 can stimulate cancer development, activate cell growth, promote migration and invasion of cancer cells, and increase the risk of metastasis formation [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…It has been confirmed that TIMP-1 is regulated by Bcl-2, which participates in the cellular apoptotic pathway [8]. However, recent reports indicate that TIMP-1 can stimulate cancer development, activate cell growth, promote migration and invasion of cancer cells, and increase the risk of metastasis formation [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…TIMPs might display a dual influence on tumor progression: either beneficial by inhibiting MMPs and impairing angiogenesis or harmful by facilitating cancer cell generation and growth [41,42,43]. Four TIMPs have been characterized in humans (TIMP-1, -2, -3 and -4).…”
Section: Introductionmentioning
confidence: 99%
“…TIMPs might display a dual influence on tumor progression: either beneficial by inhibiting MMPs and impairing angiogenesis, or harmful by facilitating cancer cell generation and growth. TIMPs have strong effects on several biological processes that lead to tumor progression, including those of stimulating cancer cell growth, survival, invasion, angiogenesis and inhibition of apoptosis [57,68,69,70]. …”
Section: The Role Of Proteinasesmentioning
confidence: 99%